The EFL Teacher's Perspective on Online English Learning Challenges - Muneeza, Aishath (Majapahit Journal of English Studies, 2024)
The purpose of this study was to detail the examination of the challenges faced by the EFL instructor at the Junior High School while teaching English as a foreign language online. The participants in this descriptive qualitative study were English teachers at the Junior High School. Using complete sampling, we were able to collect data from four English teachers. Interviews and audio recordings were utilized to gather data for this study. Interview data analysis revealed the English teacher's online pedagogical strategy for delivering lessons amid the COVID-19 pandemic. The use of learning applications as the medium for this new approach to learning was dominant. Using another app to prepare lessons, all of the English teachers at the Junior High School delivered their lessons over the WhatsApp app. Students utilized the specialized learning app, which included G-Form and Quizizz, to complete assignments and tests. The author learned that the English instructors at the Junior High School were dealing with several issues. The English teachers at the Junior High School face several challenges, including students' lack of interest and motivation, network limitations, a cap on students' use of school computers, and pupils without personal devices. Students without access to computers or cell phones may be the ones who don't respond in this instance. Thus, it all began because the student lacked access to private internet study resources.